THE EPISTEMOLOGY OF VALUES AND SUSTAINABILITY - Samian, Abdul Latif (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2017)
Science is a problem solving activity. Based on the assumption that science begins with problems, the process of macro creativity is outlined. Solutions created are preceded by intention and action. Out of the macro creative process, the dynamics of having a sustainable science, namely, the Cycle of Sustainability, is formulated. It is within this Cycle of Sustainability that innovation, i.e. the endless possibilities of micro creativity by way of mathematics is further examined as a subset of the macro creative process. It is argued that essentially the root of sustainability in science lies in having sustainable problems. Moreover, the author attempts to epistemologically argue on two issues of scientific realism: (i) the distinction between the observables and non-observables, and (ii) whether scientific claims are either true or false.